THE DANGERS OF CONSUMING LIQUOR (ALCOHOL) AMONG ADOLESCENTS - Azizah, Nur (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
The habit of drinking alcohol among teenagers is a phenomenon that often occurs in Indonesia. Many factors cause them to use their free time to drink liquor. Alcoholic drinks are all types of alcoholic beverages. Containing ethanol which are processed from agricultural products materials containing carbohydrates by means of fermentation and distillation, whether by pre-treating or not, adding other ingredients or not, or processed with by mixing concentrate with alcohol or by diluting a drink containing ethanol. The data collection method used in this research is to collect as much research data as possible from journals, articles, and other scientific writings. The purpose of this collection is to find the best research results that can be obtained by comparing more than two research results, articles, and journals with the similar theme, without the researcher having to do another research. Excessive alcohol consumption can cause negative effects to health such as brain tissue damage, liver disease, digestive system disorders, pancreatic gland disorders, muscle system disorders, sexual disorders, and fetal development disorder, as well as endocrine system disorders, nutritional metabolic system disorders, cancer risk, and metabolic disorders of the body.